Implementation of Electronic Land Rights Transfer In North Lombok District - Muhamad Tauhid; Zainal Asikin; Lalu Wira Pria Suhartana (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This thesis discusses the implementation of electronic land rights transfer in North Lombok Regency, focusing on two main problems. First, how is the process of implementing the electronic transfer of land rights at the Land Office of North Lombok Regency, and second, what is the role of the Land Deed Official (PPAT) in implementing the process. This research uses an empirical normative method with a case study approach, where data is collected through interviews, observation, and document analysis. The results show that the implementation of an electronic system in the transfer of land rights has provided efficiency in the administrative process and facilitated access for the community. Nonetheless, challenges such as limited technological infrastructure and lack of public understanding of the system still need to be overcome. In addition, the role of PPAT is vital in ensuring the validity and smoothness of the title transfer process, as well as educating the public about the applicable procedures. Based on these findings, it is recommended to increase socialization and education about the electronic title transfer system to the public, as well as provide training for PPATs. In addition, the development of adequate technological infrastructure also needs to be done to support the effectiveness of this process.